If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 1) = x Reorder the terms: (1 + X) = x Remove parenthesis around (1 + X) 1 + X = x Solving 1 + X = x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + X = -1 + x Combine like terms: 1 + -1 = 0 0 + X = -1 + x X = -1 + x Simplifying X = -1 + x
| 14y+41=139 | | 0.33333333333(21-3a)=6-a | | 3x+2x-11=84 | | 6x+0.4=6.4 | | -2x-18=-(1-2x)+4x | | 4(a+2)=14-2(3-a) | | 4n=5-5n | | 88=12x-44 | | 16x-16-8x-12=3 | | 9-4b=4-3b-6b | | 16-(2x-3)=6 | | 6x-14=2(3x-72) | | 11x-13=5(2x+4)-7 | | 45=29-2(x-3) | | 2x^2-y^2-8x+6y-2=0 | | 8a+10=50 | | 7+7k=8k+2 | | -6m+3m=4-m | | 1000=20x+100y | | nsquared+n-105=0 | | 3a-6+7-2a= | | 0.19-0.03(x+1)=-0.02(2-x) | | 9y-187+x+44=180 | | -6n=-9 | | 4x-9x+12=2x+33 | | 8a-13=4a | | r+8=-4r-7 | | 140+0.40=50-0.70 | | 8x+16=-1 | | 25x+25=3(6x+6)+7x+7 | | 2x-7x+60=3x+36 | | 7(2x-3)-4x-20=8(x-1)+3 |